Introduction to biological rhythms: A brief history of chronobiology and its relevance to parasite immunology. (2nd February 2022) - Ince, Louise Madeleine
Abstract: Almost every living organism on earth is exposed to a fluctuating environment, for example, light:dark cycles, food availability and seasonal photoperiods. Most species have therefore evolved internal timing mechanisms allowing them to anticipate these rhythmic environmental changes, obtaining a survival advantage. Circadian (24 h) rhythms, in particular, regulate multiple aspects of physiology, including sleep/wake activity, feeding rhythms and immune function. Recent studies have identified circadian rhythms in symptoms of parasite infections, rhythms in parasite schizogony and evidence that certain parasites can manipulate host rhythms. Furthermore, efficacy of anti‐parasite medications can also be modulated by timing of drug administration. Understanding the interactions between host rhythms, parasite rhythms and disease severity is crucial to fully understand how to combat infections and reduce pathology. The aim of this review is, therefore, to provide an introduction to the field of biological rhythms, give a brief history of chronobiology research and discuss the relevance of biological rhythms to parasite immunology.